Endogenous Mouse Mammary Tumor Viruses (Mtv): New Roles for an Old Virus in Cancer, Infection, and Immunity - Holt, Michael; Shevach, Ethan; Punkosdy, George (Frontiers in Oncology, 2013)
Mouse Mammary Tumor Viruses are beta-retroviruses that exist in both exogenous (MMTV) and endogenous (Mtv) forms. Exogenous MMTV is transmitted via the milk of lactating animals and is capable of inducing mammary gland tumors later in life. MMTV has provided a number of critical models for studying both viral infection as well as human breast cancer. In addition to the horizontally transmitted MMTV, most inbred mouse strains contain permanently integrated Mtv proviruses within their genome that are remnants of MMTV infection and vertically transmitted. Historically, Mtv have been appreciated for their role in shaping the T cell repertoire during thymic development via negative selection. In addition, more recent work has demonstrated a larger role for Mtv in modulating host immune responses due to its peripheral expression. The influence of Mtv on host response has been observed during experimental murine models of Polyomavirus- and ESb-induced lymphoma as well as Leishmania major and Plasmodium berghei ANKA infection. Decreased susceptibility to bacterial pathogens and virus-induced tumors has been observed among mice lacking all Mtv. We have also demonstrated a role for Mtv Sag in the expansion of regulatory T cells following chronic viral infection. The aim of this review is to summarize the latest research in the field regarding peripheral expression of Mtv with a particular focus on their role and influence on the immune system, infectious disease outcome, and potential involvement in tumor formation.